2014
DOI: 10.1152/ajpcell.00372.2013
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II modulates mouse skeletal muscle resting conductance to chloride and potassium ions and calcium homeostasis via the AT1 receptor and NADPH oxidase

Abstract: Cozzoli A, Liantonio A, Conte E, Cannone M, Massari AM, Giustino A, Scaramuzzi A, Pierno S, Mantuano P, Capogrosso RF, Camerino GM, De Luca A. Angiotensin II modulates mouse skeletal muscle resting conductance to chloride and potassium ions and calcium homeostasis via the AT 1 receptor and NADPH oxidase. Am J Physiol Cell Physiol 307: C634 -C647, 2014. First published July 30, 2014; doi:10.1152/ajpcell.00372.2013.-Angiotensin II (ANG II) plays a role in muscle wasting and remodeling; however, little evidence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 82 publications
(178 reference statements)
1
31
0
Order By: Relevance
“…This hormone has been implicated in the pathology of conditions such as cardiac failure and kidney disease-related muscle atrophy (18). The relationship between AT II and NOX2 in skeletal muscle has been evaluated by different researchers (69,169). One study suggested using pharmacological inhibitors that AT II signals via NOX2 to increase intracellular Ca 2+ in mouse EDL skeletal muscle fibers (69).…”
Section: Fig 15 Nox2-dependent Omentioning
confidence: 99%
See 1 more Smart Citation
“…This hormone has been implicated in the pathology of conditions such as cardiac failure and kidney disease-related muscle atrophy (18). The relationship between AT II and NOX2 in skeletal muscle has been evaluated by different researchers (69,169). One study suggested using pharmacological inhibitors that AT II signals via NOX2 to increase intracellular Ca 2+ in mouse EDL skeletal muscle fibers (69).…”
Section: Fig 15 Nox2-dependent Omentioning
confidence: 99%
“…The relationship between AT II and NOX2 in skeletal muscle has been evaluated by different researchers (69,169). One study suggested using pharmacological inhibitors that AT II signals via NOX2 to increase intracellular Ca 2+ in mouse EDL skeletal muscle fibers (69). Experiments in vitro using C2C12 myotubes indicated that AT II increased the ROS production by a DPI-inhibitable NOX2-dependent mechanism (305).…”
Section: Fig 15 Nox2-dependent Omentioning
confidence: 99%
“…Furthermore, electrophysiological studies showed an increase of gCl in the PKC𝜃-null mice with respect to wild-type, and a consequent reduction of muscle excitability ( Camerino et al, 2014 ). Regulation of ClC-1 channels through PKC-dependent phosphorylation appeared to be involved in the muscular effects of a number of growth factors, hormones, and drugs, including the growth hormone, insulin-like growth factor-1 (IGF-1), ghrelin, angiotensin II, growth hormone secretagogues, and statins ( De Luca et al, 1994b , 1998 ; Pierno et al, 2003 ; Cozzoli et al, 2014 ).…”
Section: Molecular Structure and Function Of Clc-1mentioning
confidence: 99%
“…, ; Cozzoli et al . ). A more physiological role of PKC‐dependent ClC‐1 inhibition was discovered when repeated firing of APs in rat muscle fibres were found to cause a more than 50% reduction in G m that was sensitive to PKC inhibition (Pedersen et al .…”
Section: Introductionmentioning
confidence: 97%